ANALYSIS OF SHARIA MARKETING STRATEGY UMRAH TRAVEL SERVICES AL ANSHOR PACITAN FROM THE PERSPECTIVE OF MAQASHID SHARIA - Hidayatul Musrifah; Duwi Habsari Mutamimah; Asis Sustiawan (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the sharia-based marketing strategy of PT Al Anshor Pacitan’s Umrah travel services from the perspective of Maqashid Shari’ah. The study is grounded in the rapid growth of the Umrah industry and the increasingly intense competition among travel agencies, while sharia principles have not yet been fully embedded in marketing practices. Marketing activities that are insufficiently transparent and potentially manipulative may conflict with the objectives of sharia in preserving pilgrims’ welfare. This research uses a qualitative approach with a case study method. Data were gathered through in-depth interviews with PT Al Anshor Pacitan staff, direct field observation, and documentation of supporting evidence. The analysis applies Imam Asy-Syatibi’s Maqashid Shari’ah framework, which covers the protection of religion (hifzh al-din), life (hifzh al-nafs), intellect (hifzh al-‘aql), lineage (hifzh al-nasl), and wealth (hifzh al-mal). The findings show that PT Al Anshor Pacitan’s marketing strategy ethically reflects sharia values, especially in service quality and worship assistance; however, these values have not been systematically integrated into promotional activities, the clarity of information on worship education and spiritual values, and the protection of pilgrims’ assets, particularly in sharia contracts.